2005
DOI: 10.1158/1055-9965.epi-04-0849
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Incidence Rates of In situ Breast Carcinomas by Histologic Type, 1980 to 2001

Abstract: Incidence rates of ductal carcinoma in situ (DCIS) and lobular carcinoma in situ (LCIS) have increased rapidly over the past several decades largely due to the increased use of mammography. However, recent data from 1987 to 1999 indicate that invasive ductal carcinoma incidence rates have remained essentially constant, whereas rates of invasive lobular carcinoma have increased 65%, with greater increases observed among postmenopausal women. Data on recent trends in DCIS and LCIS incidence rates, particularly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 34 publications
1
87
0
3
Order By: Relevance
“…Risk factors for DCIS are similar to those for invasive breast cancer, including a family history of breast cancer, fewer and/or later pregnancies, older age at menopause, and increasing age (3,4). The incidence rate for DCIS increased by a factor of 7.2 during the 1980s and began to stabilize in the 1990s (2,5). Because DCIS is detectable using mammography (2,3), and because the greatest increase in incidence rates occurred among women ages 50 years or older (5), the increase in DCIS incidence has been attributed, at least in part, to the increase in use of mammography (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors for DCIS are similar to those for invasive breast cancer, including a family history of breast cancer, fewer and/or later pregnancies, older age at menopause, and increasing age (3,4). The incidence rate for DCIS increased by a factor of 7.2 during the 1980s and began to stabilize in the 1990s (2,5). Because DCIS is detectable using mammography (2,3), and because the greatest increase in incidence rates occurred among women ages 50 years or older (5), the increase in DCIS incidence has been attributed, at least in part, to the increase in use of mammography (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Although not as common as DCIS, lobular carcinoma in situ (LCIS) incidence rates also increased 4-fold from 1978 to 1998, with the highest increase observed among women ages 50 years and older (5). However, this increase in incidence stabilized after 1991 and was minimal after 1996 (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ductal cancer in situ should increase when a screening programme is implemented (Miller et al, 2000;van Steenbergen et al, 2008) and increases have been reported from populationbased studies in the United States, Australia, Italy and the Swiss Canton of Vaud (Levi et al, 1997;Barchielli et al, 1999;Kricker et al, 2004;Li et al, 2005). In southern Switzerland, we observed, among all tumours analysed (DCIS and invasive cases), a proportion of DCIS equal to 6.4% in the period 2002 -2007, similar to that reported in two studies in the Netherlands (10% in 2000 -2004 and 7.4% in 1984 -2006), but our estimates are lower than in some US studies (13 and 15% in 1987 -2001 and 1999 -2005, respectively) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the 2000-2004 period, IBC incidence was 83.8 per 100,000 women-year and within Spain, Girona had the highest rate (95.5 per 100,000 women-year) (1). It is well known that during the recent decades ductal carcinoma in situ (DCIS) incidence has increased in several countries (2)(3)(4)(5)(6)(7). This rising has been associated with the implementation of breast cancer screening programs, but screening does not completely explain the upward trend and other factors might also play a role (2;6).…”
Section: Introductionmentioning
confidence: 99%